Effect of CuSAPO-34 catalyst preparation method on NOx removal from diesel vehicle exhausts - Zuo, Y.; Han, Lina; Bao, W.; Chang, L.; Wang, J. (Elsevier, 2013)
CuSAPO-34 samples prepared by hydrothermal synthesis (HS), pore-volume impregnation (PVI), and ion-exchange (IE) methods were characterized using X-ray diffraction, scanning electronic microscopy, atomic absorption spectroscopy, temperature-programmed reduction with hydrogen, X-ray absorption near-edge structure spectroscopy, X-ray photoelectron spectroscopy, and N2 adsorption. The selective catalytic reduction (SCR) ability over CuSAPO-34 for NOx from a simulated diesel exhaust was investigated through C3H6-SCR and NH3-SCR, before and after aging of the CuSAPO-34 catalyst. The results indicated that the sample prepared by IE had significantly better activity compared with those prepared using HS and PVI, especially in C3H6-SCR at temperatures below 300 °C. The activity of CuSAPO-34 in NO SCR was affected by the preparation method as a result of changes in the specific area (A[BET]), pore-size distribution, and the valence state of the active component. The active component of the catalyst prepared by HS was mainly Cu2+, whereas those of samples prepared by IE and PVI were mainly Cu+. Aging treatment can destroy the structure of thecatalyst, decrease its surface area, and reduce the number of active Cu components on the catalyst surface, leading to a visible decrease in catalytic activity. The CuSAPO-34 prepared using the PVI method had the smallest decrease in NO SCR activity after aging, showing that it had better anti-aging properties.